The lncRNA SOX2OT rs9839776 C>T Polymorphism Indicates Recurrent Miscarriage Susceptibility in a Southern Chinese Population - Fang, Zhenzhen; Che, Di; Qing, Shuang; Li, Qingfeng; Men, Hui; Yuan, Lianxiong; Li, Li; Gu, Xiaoqiong (Mediators of Inflammation, 2019)
Genetic susceptibility may be involved in the onset of recurrent miscarriage. Previous studies have shown that some genetic polymorphisms that regulate cell migration are associated with susceptibility to recurrent miscarriage. The SOX2 overlapping transcript (SOX2OT) may regulate the migration and invasion of multiple tumor cells and is related to susceptibility to various diseases. However, whether lncRNA SOX2OT polymorphisms are related to recurrent miscarriage susceptibility is unclear. Therefore, we investigated the relationship between the lncRNA SOX2OT rs9839776 C>T polymorphism and recurrent miscarriage susceptibility. We recruited 570 subjects with recurrent miscarriage and 578 healthy control subjects from a population in southern China and used the TaqMan method for genotyping. We found a significant association between the rs9839776 CT genotype in the SOX2OT gene and an increased risk for recurrent miscarriage (CT vs CC: adjusted OR=1.357, 95%CI=1.065−1.728, P=0.0134). However, we did not observe any significant associations between the recurrent miscarriage risk and the number of miscarriages in different age groups. In conclusion, our study indicated that the rs9839776 CT genotype may contribute to an increased risk of recurrent miscarriage in the southern Chinese population and that rs9839776 may act as a prognostic biomarker in recurrent miscarriage patients. However, an experiment-based study with a larger sample size should be performed to confirm these results.